STRATEGI KOMUNIKASI DAKWAH HUSAIN BASYAIBAN MELALUI MEDIA SOSIAL TIKTOK @BASYASMAN00 - Nafis Putri Adra'i (An-Nida : Jurnal Komunikasi Islam, 2022)
AbstractDa'wah Communication Strategy is an overall approach related to the implementation of ideas or ideas, planning and implementing a da'wah activity with the aim of conveying messages that originate from or are in accordance with the teachings of the Al-Qur'an and Sunnah, and so that other people can do good deeds according to  with the messages conveyed.  The current presence of TikTok with the second largest monthly active users after the United States is used by da'wah activists as a medium to spread da'wah to the public as Husain Basyaiban, the owner of the account @basyasman00, also uses.  This TikTok account is an account devoted to spreading da'wah by uploading videos about Islamic teachings, prohibitions and facts that are later associated with Islamic law.  The researcher raises the following issues: 1. How is the da'wah communication strategy carried out by Husain Basyaiban on social media TikTok to the audience or mad'u through his account @basyasman00?  2. Related da'wah messages conveyed by Husain Basyaiban on his TikTok social media @basyasman00 in one of the contents.  In this study the researchers raised 2 strategies, 1. Recitation strategy, which is the transfer of da'wah messages verbally and in writing.  In this recitation strategy, the author takes the example of the content "Pinjol and Paylater Lovers" in the delivery of the message, it can be concluded that debt is a very extraordinary matter, debt is allowed, only debt is owed when it is really tight and to meet needs, not lifestyle.  2. Tazkiyah strategy, this strategy is carried out so that individual changes occur.  In this Tazkiyah strategy, the author takes as an example the content "Law in Islam, fixing prayer rugs with feet" can be concluded that fixing prayer rugs with feet goes into the chapter on adab and fixing prayer rugs with feet on or off depends on which perspective the audience takes. Keywords  Propaganda Strategy, TikTok, Husain Basyaiban